Pengaruh Profitabilitas Terhadap Kebijakan Dividen Dengan Likuiditas Sebagai Pemoderasi - Zarah Puspitaningtyas; Aryo Prakoso; Andaratul Masruroh (JURNAL ADMINISTRASI BISNIS, 2019)
The purpose of this study was to analyze the effect of profitability on dividend policy by using liquidity as a moderating variable. Profitability is proxied using asset returns, the dividend policy is proxied using a dividend payout ratio, while liquidity is proxied using the current ratio. This research uses quantitative with the type of association research. The population is all 21 companies in the agricultural sector listed on the Indonesia Stock Exchange, then the sample was selected using a purposive sampling method and obtained 7 companies. Data is obtained from the annual report on the official website of the Indonesia Stock Exchange. The next data collected was analyzed using the moderated regression analysis. The results of the analysis prove that profitability influences dividend policy and liquidity moderate the relationship of profitability with dividend policy.